THE EFFECT OF MARKET ANOMALIES ON STOCK RETURNS: A STUDY ON BANKS LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2021-2023 - Noviana, Inggrid Aldia; Nilasari, Priyanti Dewi; Darusalam, Andi; Ningtyas, Mega Noerman (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to analyze the effect of market anomalies on stock returns of banking companies listed on the Indonesia Stock Exchange during the period 2021-2023. The main focus of the research is on two types of market anomalies: the day of the week effect and the week four effect. The research sample consists of 5 banking companies included in the LQ-45 index. The analysis method used is multiple linear regression with dummy variables for trading day and week. The results showed that there was no significant effect of the day of the week effect on stock returns of banking companies. All trading days have significance values above 0.05, with Monday even excluded from the model due to its very small value. Similarly, the week four effect was not shown to have a significant effect on stock returns. Although there was an indication of lower returns in the fourth week, this effect did not reach the accepted level of statistical significance (p < 0.05). In conclusion, this study did not find strong evidence to support the existence of the day of the week effect or week four effect on stock returns of banking companies on the Indonesia Stock Exchange during the period 2021-2023. These findings provide new insights into the efficiency of the Indonesian capital market, particularly in the banking sector.